2022
DOI: 10.3390/foods11101491
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous Extract of Phyllanthus emblica L. Alleviates Functional Dyspepsia through Regulating Gastrointestinal Hormones and Gut Microbiome In Vivo

Abstract: Phyllanthus emblica L. fruits were extracted by a hot water assistant with ultrasonication to obtain aqueous Phyllanthus emblica L. extract (APE). The ameliorating functional dyspepsia (FD) effect of a low dose (150 mg/kg) and a high dose (300 mg/kg) of APE was exhibited by determining the gastrointestinal motility, gastrointestinal hormones, and gut microbiome shifts in reserpine induced FD male balb/c mice. APE increased the gastrointestinal motility including the gastric emptying (GE) rate and small intesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…The extract ratio of APE was about 55%, and the total sugar and phenolic contents of APE were detected as previously described and obtained results of 23.6 and 30.77%, respectively . A further phytochemical study of APE by ultra-performance liquid chromatography with quadrupole time-of-flight mass spectrometry (UPLC–Q-TOF–MS) detected a total of 235 compounds under positive and negative ion modes, with the total ion chromatogram (TIC) exhibited in Figure S1 of the Supporting Information.…”
Section: Resultsmentioning
confidence: 64%
See 3 more Smart Citations
“…The extract ratio of APE was about 55%, and the total sugar and phenolic contents of APE were detected as previously described and obtained results of 23.6 and 30.77%, respectively . A further phytochemical study of APE by ultra-performance liquid chromatography with quadrupole time-of-flight mass spectrometry (UPLC–Q-TOF–MS) detected a total of 235 compounds under positive and negative ion modes, with the total ion chromatogram (TIC) exhibited in Figure S1 of the Supporting Information.…”
Section: Resultsmentioning
confidence: 64%
“…The selected dose of APE was based on a previous experiment, which was equivalent to about 4 and 8 g of dry P. emblica fruit/day in a 60 kg person, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The length distribution for amplicon sequence variants (ASVs) was determined ( Figure 5 A). Those in all samples would mainly range from 400 bp to 450 bp without abnormal sequence [ 27 ]. According to Figure 5 B, it could be found that there were 557 ASVs in all groups, which were comprised of core intestinal microbiota in mice.…”
Section: Resultsmentioning
confidence: 99%